(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Birth injury to the brachial plexus is referred to as obstetric brachial plexus palsy (OBPP). This study aimed to evaluate the clinical presentation and treatment outcomes of OBPP. Methods: This study was conducted in the Orthopaedic and Neonatology Department at Bangabandhu Sheikh Mujib Medical University. Infants with OBPP who presented within six months were included and initially treated with physiotherapy for up to six months. There were incomplete (neuropraxia and axonotmesis) and complete (neurotmesis) injuries. If biceps power was recovered of birth (≥M3), therapy was continued for up to 18 months. If there was no significant improvement (≤M2), surgery was performed. The final outcome was assessed after 18 months using the Mallet score, the Raimondi score, and the Medical Research Council muscle grading scale. Results: Out of 200 OBPP cases, 90% were enrolled through the outpatient department. One-fourth were identified during the neonatal period. The majority (96%) were born via vaginal delivery, with shoulder dystocia occurring in 68% of cases. Instrumental deliveries resulted in more severe injuries. Females and right-sided involvement were predominant. The overall satisfactory result with physiotherapy was observed in 65%, cases, whereas after surgery, it improved to 80%. However, when considering the upper trunk only, it approached 85% with physiotherapy and 98% after surgery (Mallet score >15, Medical Research Council grade ≥ 4, Raimondi score ≥2). For lower trunk and panplexus cases, satisfactory outcomes following physiotherapy and surgery were 41%. Conclusion: Treatment initiated within six months have ensured nearly full recovery of most upper trunk and incomplete OBPP cases, but outcomes of severely affected lower trunk and panpalsy cases was poor.